Vital Awareness: Blood Donation and Transfusion Safety (GAIMS Journal of Medical Sciences, 2024)
Background: To determine the awareness and knowledge of blood donation and transfusion reactions among various departments in our tertiary care centre.Material and methods: The cross-sectional study, conducted at ACS Medical College and Hospital in Chennai from March to May 2024, focused on 20 departments. Researchers distributed a pre-tested, self-structured e-questionnaire to the participants, who submitted their responses via email to a designated account.Results: Out of the 20 departments surveyed, 64% were Faculty, 19% Postgraduate, and 17% were Interns. A significant majority, comprising 64% faculty, reported being aware of voluntary blood donation and transfusion reactions. However, despite the awareness and access to information, only a small fraction of the participants, knew about the right period of blood donationand transfusion reactions.Conclusion: This study infers that knowledge and awareness of blood donation and transfusion reactions were relatively higher among faculty in department of surgery, obstetrics and pathology and least among psychiatry, anatomy and forensic medicine. Based on these findings, the study recommends organising regular talks and interactive sessions as essential measures to bridge the gap in knowledge, identify and dispel misconceptions, and motivate individuals for regular discussions based on blood donation and transfusion reactions. These initiatives aim to enhance awareness, clarify any misunderstandings, and foster a proper knowledge about blood donation and transfusion reactions among the patients in time of need like mass destruction like accidents and natural calamities